Feminism and Pornography: From Mainstream Pornography (Hetero-Patriarchal) to Post-Porn (Non Binary) - Valero Heredia, Ana (The Age of Human Rights Journal, 2022)
Along with prostitution, and more recently surrogate motherhood, pornography has been a contentious issue within the feminist movement ever since the 1970s. Perceived by abolitionists as the prelude to rape, for pro-Sex feminists it represents an ideal vehicle for expressing desire for women and minority sexual identities, and has a considerable transformative capacity. The latter school of thought proposes a paradigm shift and has aligned itself with Queer Theory, which advocates a non-binary approach to sexual identities through Post-porn. This study critically analyses the main arguments put forward by feminism in the field of pornography: women’s rights and the principle of no-harm.